Dielectric Properties of Foods - Buşra Tıraş; Sercan Dede; Filiz Altay (Turkish Journal of Agriculture: Food Science and Technology)
Dielectric properties of materials are used for evaluating their interactions with electromagnetic energy. Dielectric properties of food materials are required for various applications in food industry such as microwave (at 915 or 2450 MHz), radio wave (at 13.56, 27.12 or 40.68 MHz) and magnetic field processing. In order to understand the response of food materials to electromagnetic energy, dielectric parameters must be determined as a function of frequency, temperature, composition and moisture content. In this review, the dielectric properties of different food groups were listed depending on temperature and frequency ranges. In addition to the literature data of dielectric properties, the penetration depths of microwave or radio wave through food groups were calculated. The effects of temperature and composition (mostly moisture content) on dielectric properties depend on the type of the food and sometimes on frequency. However, the effect of frequency is constant; increased frequency decreased dielectric constant, loss factor and penetration depth. The lowest calculated penetration depth belonged to the fish surimi gel as 3.39 mm at microwave frequency whereas they were high generally for fats, oily seeds and flours (max was 372602 mm for corn flour). It appears that dielectric properties of foods should be investigated further depending on the interactions between frequency, temperature and composition. And then, dielectric heating based on the aim of the process can be applied accordingly. Besides, it appears that the moisture content and especially the dipole rotation and the conductivity movements of the molecules in free water content of the food are some of the most critical factors influencing the dielectric properties of food materials.